P-glycoprotein confers methotrexate resistance in 3T6 cells with deficient carrier-mediated methotrexate uptake. - de Graaf, D (1996)
P-glycoprotein (Pgp), a transmembrane efflux pump encoded by the MDR1 gene, transports various lipophilic drugs that enter the cell by passive diffusion through the lipid bilayer. Pgp-expressing multidrug-resistant cell lines are not usually cross-resistant to a hydrophilic antifolate methotrexate (MTX). MTX enters cells primarily through a folate carrier, but passive diffusion becomes the primary mode of MTX uptake in carrier-deficient cells. To test if a deficiency in MTX carrier would allow Pgp to confer resistance to MTX, a MTX carrier-deficient cell line (3T6-C26) was infected with a recombinant retrovirus expressing the human MDR1 gene. The infected 3T6-C26 cells showed increased survival in MTX relative to uninfected cells. Multistep selection of the infected cells with vinblastine led to increased Pgp expression and a concomitant increase in resistance to MTX. MTX resistance of Pgp-expressing 3T6-C26 cells was reduced by Pgp inhibitors, including a Pgp-specific monoclonal antibody UTC2. In contrast, the expression and the inhibition of Pgp had no effect on MTX resistance in 3T6 cells with normal carrier-mediated MTX uptake. Thus, a deficiency in the MTX carrier enables Pgp to confer resistance to MTX, suggesting that hydrophilic compounds may become Pgp substrates when such compounds enter cells by passive diffusion.